Digital transformation with sMOOC: a proposal based on educommunication - Santos-Martínez, Clara Janneth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The study proposes the digital transformation of 3 expanded classrooms (non-formal education within the formal one), which are training models in the use of school media in Barranquilla (Colombia). In response to the detected needs, a sMOOC (Social Massive Open Online Course) is designed as a virtualization educommunication scenario, in line with the Digcomp 2.2 citizen competency framework, which consolidates a learning community in the use of ICT according to the context of the XXI century. Methodology: qualitative approach. Mixed design of a case study and phenomenology. Intentional sample.